EFFECTS OF A FLOOD HAZARD ON SOCIAL AND ECONOMIC LIFE OF RURAL INHABITANTS - Wioletta Knapik (Acta Scientiarum Polonorum. Oeconomia, 2014)
Climate changes, resulting in occurrence of extreme natural phenomena that do not bypass our country and continent, are the background of the research. In Poland, the areas most endangered with floods are located in the southern part of the country. The subject of author's research is flood hazard and its effect on the strength of social bonds and community actions undertaken by rural inhabitants (communes Gnojnik, Skarbimierz, and Sławatycze). These are the inhabitants living within the flooded areas, both people directly affected by the flood and also their neighbors who provided help. In the examined period (2008-2011), the selected communes experienced floods at least twice, with the assumption that not all the respondents were affected by it. The main research method used in the study was systematic comparison. Despite of the existing flood hazard, the respondents feel secure in their place of residence and do not wish to relocate; they are deeply bounded with it, first of all because of their families and close friends who also live there; They appreciate people whom they can trust. The majority of the respondents from all communes declared their positive attitude towards strangers. The respondents from the examined communes exhibited particularly large trust towards their commune leaders.